Prolonged dual antiplatelet therapy after drug-eluting stent implantation in patients with diabetes mellitus: A nationwide retrospective cohort study - Lee, Seung-Jun; Choi, Dong-Woo; Kim, Choongki; Suh, Yongsung; Hong, Sung-Jin; Ahn, Chul-Min; Kim, Jung-Sun; Kim, Byeong-Keuk; Ko, Young-Guk; Choi, Donghoon; Park, Eun-Cheol; Jang, Yangsoo; et al. (Frontiers in Cardiovascular Medicine, 2022)
Background Optimal duration of dual antiplatelet therapy (DAPT) in patients with diabetes mellitus (DM) who have undergone drug-eluting stent (DES) implantation is not clearly established. This study sought to impact of DAPT duration on real-world clinical outcome in patients with or without DM. Methods Using a nationwide cohort database, we investigate the association between DAPT duration and clinical outcome between 1 and 3 years after percutaneous coronary intervention (PCI). Primary outcome was all-cause death. Secondary outcomes were cardiovascular death, myocardial infarction, and composite bleeding events. After weighting, 90,100 DES-treated patients were included; 29,544 patients with DM and 60,556 without DM; 31,233 patients with standard DAPT (6–12 months) and 58,867 with prolonged DAPT (12–24 months). Results The incidence of all-cause death was significantly lower in patients with prolonged DAPT [8.3% vs. 10.5% in those with standard DAPT, hazard ratio (HR) 0.78, 95% confidence interval (CI) 0.72–0.84] in diabetic patients and non-diabetic patients (4.5% vs. 5.0% in those with standard DAPT, HR 0.89, 95% CI 0.83–0.96). The incidence of composite bleeding events was 5.7% vs. 5.4%, respectively, (HR 1.07, 95% CI 0.96–1.18) in diabetic patients and 5.6% vs. 5.0%, respectively, in non-diabetic patients (HR 1.13, 95% CI 1.05–1.21). There was a significant interaction between the presence of DM and DAPT duration for all-cause death (p for interaction, pint = 0.01) that further favored prolonged DAPT in diabetic patients. However, there was no significant interaction between the presence of DM and DAPT duration for composite bleeding events (pint = 0.38). Conclusions This study showed that prolonged rather than standard DAPT might be clinically beneficial in diabetic patients with DES implantation. Trial registration ClinicalTrial.gov (NCT04715594).